2013
DOI: 10.1007/s12192-012-0360-4
|View full text |Cite
|
Sign up to set email alerts
|

Probing the transient interaction between the small heat-shock protein Hsp21 and a model substrate protein using crosslinking mass spectrometry

Abstract: Small heat-shock protein chaperones are important players in the protein quality control system of the cell, because they can immediately respond to partially unfolded proteins, thereby protecting the cell from harmful aggregates. The small heat-shock proteins can form large polydisperse oligomers that are exceptionally dynamic, which is implicated in their function of protecting substrate proteins from aggregation. Yet the mechanism of substrate recognition remains poorly understood, and little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…However, the truncations also significantly affect the structural integrity of sHSPs and therefore, the exact roles of the corresponding regions for substrate-binding could not be unambiguously assigned. A more reliable strategy based on chemical crosslinking coupled with mass spectrometry was successfully applied to the characterization of the substrate-binding regions of M. tuberculosis Hsp16.3, plant Hsp21, and mammalian aA-crystallin, aB-crystallin, and Hsp22 [105][106][107][108][109], revealing that the N-terminal part of the a-crystallin domain and the N-terminal arm are the major regions for substrate binding. Notably, these substrate-binding regions appear to contain both polar and non-polar amino acids.…”
Section: Multi-type Residues Of Shsps Participate In Binding Substratmentioning
confidence: 99%
“…However, the truncations also significantly affect the structural integrity of sHSPs and therefore, the exact roles of the corresponding regions for substrate-binding could not be unambiguously assigned. A more reliable strategy based on chemical crosslinking coupled with mass spectrometry was successfully applied to the characterization of the substrate-binding regions of M. tuberculosis Hsp16.3, plant Hsp21, and mammalian aA-crystallin, aB-crystallin, and Hsp22 [105][106][107][108][109], revealing that the N-terminal part of the a-crystallin domain and the N-terminal arm are the major regions for substrate binding. Notably, these substrate-binding regions appear to contain both polar and non-polar amino acids.…”
Section: Multi-type Residues Of Shsps Participate In Binding Substratmentioning
confidence: 99%
“…Whereas the exact role of the fl exible C-terminal extension in binding substrate proteins is still in debate (Carver and Lindner 1998 ;Smulders et al 1996 ;Jehle et al 2010 ;Saji et al 2008 ;Treweek et al 2007 ;Jaya et al 2009 ;Jiao et al 2005b ;Fu et al 2013b ), it is well established that the structurally disordered N-terminal arm serves as a principal substrate-binding region (Fu et al , 2013bSharma et al 1997 ;Jaya et al 2009 ;Lambert et al 2013 ). In this context, sHSPs appear to dominantly utilize their disordered N-terminal arms for substrate-binding, and thus allow them to present diverse geometries for substrate-binding.…”
Section: Disorder-adapting-disorder For Shsp-substrate Recognition Anmentioning
confidence: 99%
“…Studies by truncation or by chemical crosslinking showed that the three characteristic domains of sHSPs are all crucial for the chaperone functional integrity (Merck et al 1993b ;Fu and Chang 2006a ;Fu et al 2005 ;Basha et al 2006 ;Giese and Vierling 2004 ;Leroux et al 1997b ;Jiao et al 2005b ;Lentze et al 2003 ;Ghosh et al 2006 ;Saji et al 2008 ;Strozecka et al 2012 ;Studer et al 2002 ;Treweek et al 2007 ;Fu and Chang 2006b ;Lambert et al 2013 ;Shemetov and Gusev 2011 ). However, these studies cannot reveal the exact role of each amino acid residue for substrate-binding.…”
Section: Structural Diversity and Spatial Chaos Of Substratebinding Rmentioning
confidence: 99%
“…We have repeatedly seen in proteolysis experiments that the N-terminal domain in Hsp21 is rapidly degraded, behaving as intrinsically disordered proteins (Bardwell and Jakob 2012 ;Tompa and Csermely 2004 ) and in various functional in vitro assays Hsp21 displays the typical properties of a molecular chaperone, suppressing the aggregation of heat-sensitive model substrate proteins and of fi brillation-prone peptides (unpublished data). Chemical crosslinking and mass spectrometry suggest an interaction between the disordered N-terminal region of Hsp21 and the C-terminal presumably unfolding part of the temperature-sensitive substrate protein malate dehydrogenase (Lambert et al 2013 ).…”
Section: The Chloroplast-localized Shsp Hsp21mentioning
confidence: 99%